(untitled) (Al-Farooq Journal of Sciences, 2026)
The distinction between language learning and language acquisition has been central to debates in applied linguistics and second language acquisition (SLA) for several decades. Early theorists, such as Stephen Krashen, argued for a strict separation between unconscious acquisition and conscious learning, while others (including Rod Ellis, Jack C. Richards, Michael Long, Merrill Swain, Lev Vygotsky, Jean Piaget, Diane Larsen-Freeman, and Richard Schmidt) have challenged, refined, or expanded this dichotomy. Drawing on cognitive, interactionist, sociocultural, and complexity and dynamic theory perspectives, this paper argues that the binary distinction between learning and acquisition is theoretically insufficient. Instead, contemporary SLA research supports a dynamic systems view in which language develops through an interplay of implicit and explicit processes. The paper concludes that the term second language development (SLD) offers a more accurate and comprehensive conceptualization than second language acquisition (SLA). Moreover, this paper examines the pedagogical implication in EFL teaching arguing that the view of language as a fixed body of knowledge to be transmitted or ‘acquired’ in linear stages should transcend to the view of language as a dynamic, evolving, adaptive process shaped by interaction, context, identity, emotions, and social participation. On the surface level it might appear as a terminological shift but it carries a deeper theoretical and epistemological concept; eventually leading to pedagogical implications that cause a change in English as a Foreign Language (EFL) education and in how learners learn English.